2022
DOI: 10.1155/2022/4619760
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Cannabidiol on Chemotherapy-Induced Oral Mucositis via the Nrf2/Keap1/ARE Signaling Pathways

Abstract: Oral mucositis (OM) is a common complication during chemotherapy characterized by ulceration, mucosa atrophy, and necrosis, which seriously interferes with nutritional intake and oncotherapy procedures among patients. However, the efficacy of current treatments for OM remains limited. Cannabidiol (CBD) is a natural cannabinoid with multiple biological activities, including antioxidant and anti-inflammatory potential. In this study, we aimed to investigate the chemopreventive effects and mechanisms of CBD in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 49 publications
0
20
0
2
Order By: Relevance
“…p62 links autophagy and Nrf2/Keap1/ARE signaling, which is a redox sensitive signaling axis that functions to protect cells against oxidative stress and environmental toxicants ( 57 ). Recent reports suggest that CBD can activate the Nrf2/Keap1/ARE pathway and attenuate production of ROS ( 58 , 59 ). P62 is also a target gene for Nrf2 transcription factor, which binds to the ARE (Antioxidant response element) in p62 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…p62 links autophagy and Nrf2/Keap1/ARE signaling, which is a redox sensitive signaling axis that functions to protect cells against oxidative stress and environmental toxicants ( 57 ). Recent reports suggest that CBD can activate the Nrf2/Keap1/ARE pathway and attenuate production of ROS ( 58 , 59 ). P62 is also a target gene for Nrf2 transcription factor, which binds to the ARE (Antioxidant response element) in p62 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that UV-irradiated keratinocytes treated with CBD (1 μM) have stimulated the Nrf2 pathway and at the same time downregulation of the NF-κB pathway along with increased expression of phosphorylated IκBβ [ 15 ]. Moreover, a similar effect of CBD (30 μM) on the Nrf2 pathway (including Keap1 downregulation and Nrf2 activation) correlated with blanking the NF-κB pathway by lowering the TNF-α was also observed in animals with oral mucositis [ 122 ]. On the other hand, CBD (2.5 μM) did not affect the level of NF-κB family member p50 in response to TNF - α in C2C12 muscle cells [ 123 ].…”
Section: The Role Of Cannabidiol In the Nrf2 - Nf-κb Crosstalkmentioning
confidence: 99%
“…To our knowledge, this is the only secondary study that analyzes cannabinoid effectiveness as supplementation therapy in IBD and gives an estimation of CDAI reduction. The only other meta-analysis on the topic was performed by Doeve et al, [ 24 ] who included in their work both experimental and observational trials, but could not give an estimation of disease activity index variation. The present one is the first work that gives a separate estimation of overall RR of successful cannabinoid supplementation in both CD and UC.…”
Section: Discussionmentioning
confidence: 99%
“…Some pharmaceutical agents have already been investigated, and have shown some potential in pre-clinical studies [ 23 ]. In particular, Cannabidiol has been proven effective as a therapeutic option for oral wound healing in vivo mouse models, both in Chemotherapy-Induced Oral Mucositis (via the Nrf2/Keap1/ARE Signaling Pathways) and on wound-induced ulcers [ 24 , 25 ]. Some patients also use cannabinoids in order to alleviate their symptoms, and while effective, a higher usage has been associated with a higher risk of surgery in patients with Crohn’s disease [ 26 ].…”
Section: Introductionmentioning
confidence: 99%